PENGARUH MOTIF PENGGUNAAN APLIKASI RRI DIGITAL TERHADAP MINAT DENGAR DI RADIO REPUBLIK INDONESIA - Sulistya, Yulia Putri; Wahyuni, Jauhar (The Commercium, 2024)
Radio Republik Indonesia continues to strive to continue transforming in the digital era by continuing to develop the RRI Digital streaming radio application which makes RRI different from other radio stations. At RRI Digital, users are given the choice to access content that suits their desires, interests and needs. Therefore, media users have certain motives to fulfill their needs. The motive for using media needs to be questioned whether this motive can be satisfied after accessing the media. This is in accordance with the Uses and Gratifications theory, which states that audiences actively choose media that best suits their needs. After rebranding, the program previously called RRI Play Go has now changed its name to RRI Digital. Users of this program can quickly access news, music, podcasts and RRI broadcasts throughout Indonesia at any time and from any location. The aim of this research is to find out whether interest in listening to Radio Republik Indonesia is influenced by the reasons behind using the RRI Digital application. This type of research is quantitative and uses a purposive sampling approach by selecting 100 respondents for the survey using basic linear regression analysis techniques. Research findings show that interest in listening to Radio Republik Indonesia is influenced by the reasons behind using the RRI Digital application.